(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Teungku Chiek Dirundeng said that the religion and state an inseparable unit, unlike Soekarno, who saw religion and the state as two separate entities. This research will examine the concept of religion and state in Teungku Chiek Dirundeng perceptive. This research is a library research that used the Historical-Philosophical Approach. The results of this study show that Teungku Chiek Dirundeng is not only a religious leader, but also a warrior in Aceh. From the side of a religious figure, Teungku Chiek Dirundeng is a figure who has carried out many religious activities. From the side of the warrior, Teungku Chiek Dirundeng has tried hard to defend his homeland from the Dutch colonialists. The perceptive of the state as an area that must be defended in order to carry out religious teachings perfectly has given rise to the concept of "sabil war," which is able to raise the spirit of the Acehnese people to fight the Dutch. This concept has succeeded in motivating the people not to give up against Dutch colonialism.